Characterizing the Geometry and Quantifying the Impact of Nanoscopic Electrocatalyst/Semiconductor Interfaces under Solar Water Splitting Conditions. Issue 11 (2nd February 2022) - Hemmerling, John R.; Mathur, Aarti; Linic, Suljo
Abstract: The materials that are receiving the most attention in photoelectrochemical water splitting are metallic nanoparticle electrocatalysts (np‐EC) attached to the surface of a semiconductor (SC) light absorber. In these multicomponent systems, the interface between the semiconductor and electrocatalysts critically affects performance. However, the np‐EC/SC interface remains poorly understood as it is complex on atomic scales, dynamic under reaction conditions, and inaccessible to direct experimental probes. This contribution sheds light on how the electrocatalyst/semiconductor interface evolves under reaction conditions by investigating the behavior of nickel electrocatalysts (as nanoparticles and films) deposited on silicon semiconductors. Rigorous electrochemical experiments, interfacial atomistic characterization, and computational modeling are combined to demonstrate critical links between the atomistic features of the interface and the overall performance. It is shown that electrolyte‐induced atomistic changes to the interface lead to (1) modulation of the charge carrier fluxes and a dramatic decrease in the electron/hole recombination rates and (2) a change in the barrier height of the interface. Furthermore, the critical roles of nonidealities and electrocatalyst coverage due to interfacial geometry are explored. Each of these factors must be considered to optimize the design of metal/semiconductor interfaces which are broadly applicable to photoelectrocatalysis and photovoltaic research. Abstract : Electrochemical testing, atomic interfacial characterization, and computation modeling are used to elucidate the role of electrocatalyst/semiconductor interfaces under photoelectrochemical water oxidation conditions. The mechanisms by which the interface impacts the photovoltage, and the critical design parameters that must be optimized to improve performance, are unearthed. Light is also shed on the impact of operating conditions on the interface.